Microplastic burden in Africa: A review of occurrence, impacts, and sustainability potential of bioplastics - Emmanuel Sunday Okeke; Oluwatosin Atinuke Olagbaju; Charles Obinwanne Okoye; Charles Izuma Addey; Kingsley Ikechukwu Chukwudozie; Joseph Onyekwere Okoro; Gideon Gywa Deme; David Ewusi-Mensah; Eghosa Igun; Onome Ejeromedoghene; Elijah Chibueze Odii; Olayinka Oderinde; et al. (Chemical Engineering Journal Advances, 2022)
Although the use of plastics varies across different regions, Africa is ranked second after Asia as an indiscernible consumer of plastics that break down into microplastic. Moreover, little is known about the impact of these microplastics across the African continent. This review provides insight into what microplastics are and their impact on the environment across Africa. The mismanagement of plastic waste is at its peak in Africa, as the continent mismanages over 70% of daily generated waste on average through activities such as tourism, fishing, and waste transport from one end to the other through waterways. Regarding the impact of microplastics on the environment, we found that they facilitate severe environmental consequences, such as the development of metal toxicity within aquatic and terrestrial organisms, disruptions of the food chain in the ecosystem, and public health challenges to humans who consume seafood. Alternatively, bioplastics are promising biodegradable and environmentally friendly plastic materials that could be crucial in expanding Africa's plastic industry. Furthermore, the continent has some widely spread biobased renewable raw materials that can be harnessed for developing bioplastics. Therefore, biomass-based polymers are promising alternative plastic feedstocks for producing plastics because they can readily biodegrade and break down in industrial compost facilities.